Implementation of the Muwahhadah Method in Equalizing the Rhythm of Qur'an Reading at the Tebuireng Islamic Boarding School - Hasanatun Nadiyya; Rofiatul Hosna; Adibah (STAI Terpadu Yogyakarta, 2025)
This study aims to examine the potential application of the Qira'ah Muwahhadah method in improving the quality of Qur'an learning at Pondok Putri Islamic Boarding School Tebuireng. The research approach used is qualitative with in-depth interview methods and direct observation. The results of the study show that the Qira'ah Muwahhadah method has great potential in improving the quality of Qur'an learning, especially in the aspects of fluency, understanding, and sustainability of learning. However, the implementation of this method still faces various challenges, such as limited teaching time, inadequate facilities, and low confidence of teachers. The implications of these findings suggest that the Qira'ah Muwahhadah method can be an innovative solution in improving the quality of Qur'an learning, but it requires adequate support to optimize the results. Therefore, this study recommends the need to improve the quality of training for teachers, provide more complete supporting facilities, and develop strategies to overcome existing obstacles. With these steps, it is hoped that the Qira'ah Muwahhadah method can be applied effectively and sustainably in various Islamic-based educational institutions